Intraoperative Control of Rotational Forces During Sliding Hip Screw Insertion: A Novel Surgical Technique. Issue 1 (March 2016) - Saper, David; Tornetta, Paul
Abstract : A sliding hip screw construct is most efficacious with an anatomic reduction to allow maximal interdigitation of the fracture site. We present a novel technique to control rotation during sliding hip screw insertion.